Multicultural Teacher Preparation in Practice: A Hermeneutical Disposition - Bilal, Muhammad; Abbas Rizvi, Syed Asad (European Scientific Journal, ESJ, 2016)
It is a fact that learning to teach is basically a social and practical activity that is supported and informed by theoretical reflections. Field experience and realities should be the core component of any teacher preparation program. That is why, most of the teacher education programs based on theory into practice model. The main aim of this research is not to reject this model, but to sketch out an alternative way of teacher preparation that is based upon teacher’s own context and socio cultural settings or in other words teacher preparation must be organized Hermeneutically. The hermeneutical approach of Hans-Georg Gadamer, is not only of philosophical importance but contains practical implications also. The concepts of understanding, interpretation and application are the core concepts of teacher preparation. In contrast to adopting an entire theory as the guiding principle to the whole content and practice of teacher preparation courses, this research argue for the focus to be on inculcating a hermeneutic disposition in all teachers preparation programs and courses. Hermeneutics is basic to human interaction, especially in dealing with student-teachers belongs to diverse socio-cultural settings or multicultural environment. The main argument or focus of this research is that it is necessary that the teacher preparation programs must be consider the problem of multiculturalism (inter and intra cultural). Multicultural Teacher Preparation (MTP) or hermeneutical mode of teacher preparation plays an important role in the preparation of teachers. It will be helpful for teachers to develop a deep level understanding of students needs belongs to various backgrounds and perspectives, not through applying a predetermined model of classroom activities, but through helping future teachers to recognize their own prejudices and how these help to determine their understandings of diversity in their future classrooms. Developing a hermeneutic disposition in teachers training facilitates and enrich experience of future teachers. A mixed method design was used to conduct the study.